Reperfusion therapy of ischemic stroke - L. B. Novikova; A. P. Akopyan; K. M. Sharapova; E. M. Kolchina (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To assess the main results of thrombolytic therapy (TLT) in patients with ischemic stroke (IS) in the Regional Vascular Center at the premises of Emergency Hospital in Ufa.Material and methods. A retrospective study of the TLT use was carried out in patients with acute cerebrovascular accident (CVA) who were admitted to the hospital from January 1, 2014 to December 26, 2017 The inclusion criteria were all IS cases in which patients received alteplase (actilyse) in accordance with the thrombolysis protocol.Results. There was a decrease in the number of patients with acute CVA hospitalized in the department for CVA patients. The proportion of ischemic stroke increased from 76,3% in 2014 to 79,1% in 2017 Annually, there was an increase in the number of patients with onset-to-door time <4,5 hours and reduction in door-to-needle time for thrombolysis from 1,5 hours in 2014 to 52,5 minutes in 2017 The share of TLT procedures increased from 2,4% in 2014 to 7,3% in 2017 In total, 180 (4,8%) procedures was performed. In 96% of patients there was a significant regression of neurologic deficit according to the NIH Stroke Scale after reperfusion therapy for the entire period. A complication of TLT was hemorrhagic transformation (HT), which was symptomatic in 8 (4,4%) patients. The highest 30-day mortality rate after TLT was in 2014 — 7,7%, the lowest in 2015 — 2,3%. For the entire study period, this parameter was 3,8%.Conclusion. During the study period of TLT in IS patients, there was a positive trend in the number of patients with onset-to-door time <4,5 hours and a reduction in door-to-needle time for thrombolysis. We also observed increase of total thrombolysis procedure amount, and most patients had significant neurological deficit improvement. The incidence of significant complications and mortality after TLT was lower than in the Russian Federation. The safety of TLT is based on adherence to uniform patient selection criteria and thrombolysis protocol. A personalized approach in selecting patients for TLT is a predictor of the hemorrhagic complications. The adherence to the thrombolysis algorithm and guidelines of patient management after thrombolysis contributes to the successful use of this treatment method in IS patients.